Analisis Strategi Pemasaran Untuk Meningkatkan Daya Saing Produk UMKM Ayam Dan Ikan Bareng (Bakar Goreng) - Aef Saefullah; Anggi Pasca Arnu (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Small and Medium Enterprises (MSMEs) play an important role in working on a country's economy, which has recently become one of the main drivers of public monetary development. Currently, business conditions are becoming more serious. SMEs that can make a due, obviously use techniques. The motivation behind this research is to decide on testing the advertising system used by SMEs with chicken and fish (Bakar Goreng) in increasing the intensity of their goods. The exploration strategy used is an elucidating strategy with a subjective methodology with interview and examination procedures. The side effects of this study are . The advertising system used in expanding the seriousness of MSME products in BaReng is to do a showcase division but without looking at the market division as far as buyer behavior, without special rules, and not limiting customer time. Deciding to display the time on important occasions, for example, before Eid or Christmas. Utilize a mix of advertising as far as quality of goods and cost of goods. Face the competition by offering items with attractive bundling and reasonable costs. The supporting variables for the MSME promotion system in expanding the seriousness of MSME products are the availability of raw materials and extraordinary product quality. Meanwhile, the repressive elements for MSMEs in presenting procedures in expanding the intensity of MSME items are the market network which is still small, the absence of the use of online media tasks as an advertising tool, and the tight competition.